DETERMINANTS OF ABANDONED HOUSING PROJECTS IN MALAYSIA - Dzuljastri Abdul-Razak (UNISSULA, 2016)
The issues of abandoned housing projects are not new in Malaysia.Without proper measures to tackle, they will continue to haunt homebuyers. This study examines responses of 328 customersobtained bymeans of self-administered questionnaires. Four variables namelylack of justice and equity, methods of computing and pricing, natureof contract and lack of legal and governance were used as variables.The results indicated that all the hypothesized relationships aresupported. Of these, the nature of contract was found to be the maincause of the problem. The results contributes to the scanty empiricalresearch in this area. It also benefits managers of Islamic banksto address issues that are affectingabandoned housing projects inMalaysia.